Location-Routing Problem Analysis (Case Study: Natural Disaster Risk Mitigation in Pangandaran District) - Kusuma Ningrum, Nabila Fajri; Kharisma, Muhammad Welano; Agustin, Rifqi Rahmadanti; Redi, Anak Agung Ngurah Perwira; Liferda, Rahmad Inca (Institut Teknologi Sepuluh Nopember, 2020)
Geographically, Indonesia is surrounded by three continental plates which cause the emergence of earthquake pathways, a series of active mountains throughout Indonesia, and the inevitable tsunami. Considering the large potential and risks arising from such natural disasters, disaster mitigation is important to minimize the risk, one of which is through humanitarian logistics. Pangandaran Regency is the focus of this study given that in 2018, Pangandaran is the 16th most disaster-prone area out of 514 districts/cities in Indonesia and the 5th out of 27 districts/cities in West Java. It would be a high risk if mitigation, preparation, and logistics response in Pengandaran is not well planned. The focus of this research is to determine the strategic location of disaster emergency response warehouse placement with the Set Covering Problem algorithm and determine the optimal route to the location of refuge using the Nearest Neighborhood Heuristics, Local Search, and Simulated Annealing algorithms.Â